ANALISIS RESIKO USAHA IKAN MUJAIR POLA KERAMBA JARING APUNG (KJA) DI KECAMATAN WARKUK RANAU SELATAN KABUPATEN OKU SELATAN (JASEP, 2021)
This study aimed to the analysis of mujair fish industry with Keramba Jaring Apung model in Warkuk Ranau Selatan, Ogan Komering Ulu Selatan of Regency. The location is determined by purposive. Proportionated Stratified Random Sampling as the sample method, take 25 samples of 81 samples of South warkuk Ranau. The result showed that corn farming income is Rp 148.459.460 per year. From risk analysis,the study finds that corn farming will not face risk significantly, which is indicated by the coefficient of variation of 0,0892004791 with a lower limit value of the income is Rp 121.974.150,081. Keywords : income, the risk of fishery farming